2016
DOI: 10.4172/2380-5439.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Beliefs and Barriers of Organ Donation among Saudis in Madinah City, Saudi Arabia

Abstract: Background: Although organ transplantation is considered as the only preferable treatment for end-stage organ disease, there are not many organ donors among Saudis.Objectives: To assess knowledge and attitude of Saudis in Madinah, Saudi Arabia, towards organ donation and to determine factors intervene with willingness of family to donate a member's organ. Methods:A cross-sectional study, data were collected through a valid structured interview questionnaire from 290 participants during organ donation campaign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Healthcare professionals have an important task in educating and motivating the general population. 2,17 When comparing the various professional groups, it was observed that among all the healthcare workers, nurses and paramedics have maximum hour contact with patients, from their admission until discharge, as well as during follow-up. Their personal knowledge and attitudes on organ donation can play a crucial role in the decision-making process of potential patient/attenders regarding such.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals have an important task in educating and motivating the general population. 2,17 When comparing the various professional groups, it was observed that among all the healthcare workers, nurses and paramedics have maximum hour contact with patients, from their admission until discharge, as well as during follow-up. Their personal knowledge and attitudes on organ donation can play a crucial role in the decision-making process of potential patient/attenders regarding such.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Ghaida Jabri et al [3] also revealed the same. In this study about, 138(76.7%) reported that donor consent is required for living donation and 165(91.6%) reported that family consent is required for organ donation after death.…”
Section: Discussionmentioning
confidence: 52%
“…About 15 (8.30%) participants never thought about organ donation. Whereas in the study conducted by Ghaida Jabri et al (2016) lack of awareness (21.7%), family refusal (20.6%) and fear of unknown (19.7%) were the most important barriers of organ donation [3]. This study revealed that 118 (80.82%) had appropriate knowledge towards organ donation which reflected in their attitude.…”
Section: Original Research Articlementioning
confidence: 61%
See 2 more Smart Citations